Results of Open Rhinoplasty in Patients with Nasal Deformities - Bernardo Canto Vidal; Ángel Viera Dosil; Dayamí Aguilar Colina; Bienvenido Mesa Reinaldo; Enma Gil Ojeda (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2017)
Foundation: Rhinoplasty is a surgical procedure to solve aesthetic and functional problems. Although it is refused by many surgeons due to the external incision of the columella, it is highly useful in difficult cases. Objective: To describe the results of open rhinoplasty in patients with nasal deformities. Methods: A descriptive study was realized, of patients operated through the technique of open rhinoplasty in the period 2005-2012 in the Hospital Gustavo Aldereguía Lima. Cienfuegos. The variables analyzed were: age, sex, race, and type of incision. Results: Most of the patients were under 30 years old; the lowest age was 14 and the maximum 50 years old. The type of incision mostly used was inverted V. In none of the operated patients a keloid appeared. The 100 % of patients manifested a high degree of satisfaction with respects to the results of the operation. Conclusion: Open rhinoplasty offers a series of advantages which guarantee the success of the surgical intervention to the surgeon. If the necessary measures are adopted the surgical risk is minimal, similarly the probabilities of appearance of a keloid scar which is more frequent in mestizo and black patients who are also those who demand this type of surgery in the studied series.